Isolation and Identification of Lactic Acid Bacteria from the Washing Water of Mayas Rice, a Traditional Mountain Rice from East Kalimantan: Isolasi Dan Identifikasi Bakteri Asam Laktat Dari Air Cucian Beras Gunung (Beras Mayas) Khas Kalimantan Timur - Amanda, Rezti; Rijai, Laode; Arifuddin, Muhammad (Jurnal Riseta Naturafarm, 2025)
Rice washing water contains carbohydrates, vitamins, and minerals that serve as potential substrates for the growth of Lactic Acid Bacteria (LAB). This study aims to isolate and characterize LAB from the traditional East Kalimantan rice variety Beras Mayas. LAB isolation was performed using De Man Rogosa and Sharpe (MRS) Agar, followed by successive purification to obtain pure cultures. Identification of the isolates involved macroscopic and microscopic observations, Gram staining, and a series of biochemical assays. Three distinct LAB isolates, designated A, B, and C, were obtained. Isolates A and B exhibited circular colonies with yellowish-white pigmentation and undulate margins, suggesting affiliation with the genus Lactobacillus. Isolate C formed circular white colonies with entire margins, indicating a possible relationship with the genus Streptococcus. Biochemical testing revealed that all three isolates were negative for catalase, gelatin hydrolysis, motility, and indole production. In the Triple Sugar Iron Agar (TSIA) test, all isolates fermented glucose, lactose, and sucrose, producing yellow coloration in both the slant and butt portions of the medium. These results suggest that the isolates are homofermentative LAB.